Testing a new listening-room - Bjarne LANGVARD; Henrik MØLLER; Gustaw BUDZYŃSKI (Archives of Acoustics, 2015)
New listening-rooms purposely designed and built are relatively seldom described in the literature, nevertheless problems arise especially when assessing their acoustic quality. Such problems are considered on the example of a new listening-room of the Acoustic Laboratory at the Aalborg University in Denmark. Results of the measurements and testing are discussed and some more general conclusions presented.